The political economy of European integration - Spolaore, Enrico (Coventry, 2015)
"This paper discusses the process of European institutional integration from a political economy perspective, linking the long-standing political debate on the nature of the European project to the recent economic literature on political integration and disintegration. First, we introduce the fundamental trade-off between economies of scale associated with larger political unions and the costs from sharing public goods and policies among more heterogeneous populations, and examine the implications of the trade-off for European integration. Second, we describe the two main political theories of European integration - intergovernmentalism and functionalism - and argue that both theories capture important aspects of European integration, but that neither view provides a complete and realistic interpretation of the process. Finally, we critically discuss the successes and limitations of the actual process of European institutional integration, from its beginnings after World War II to the current crisis."